Diagnostic efficacy of FNAC by liquid based technique versus conventional smear in lung and mediastinal masses - Singh, Rekha; Mittal, Vani; Bali, Irbinder Kour; Arora, Sunil; Kumar, Raj (International Journal of Research in Medical Sciences, 2020)
Background: Fine Needle Aspiration Cytology (FNAC) has proven to be less costly and less invasive procedure than biopsy for diagnosing benign and malignant lesions. Of the two methods liquid based cytology (LBC) and conventional cytology (CC), LBC has been standardized as more efficacious in reporting in Gynaecological cases. But, this is still lacking in non-gynaecological cases and many studies are now focusing on studying LBC due to its proven advantages in Pap smear evaluation. Methods: An observational study of 72 patients with lung mass and 11 with mediastinal mass was done for a period of six months in a tertiary care hospital in Gurugram to compare the diagnostic efficacy of LBC and CC in fine needle aspirates from lung/mediastinal mass. Results: Of the 83 cases, reporting of LBC was adequate in 75 cases and CC in only 53 cases. LBC was better when differentiating malignant and benign lesions than CC. CC smears had better cellularity in comparison to LBC smears (36%), but rest cytological features of cytoplasmic detailing, cell architecture, less background debris and blood were all more appreciable in LBC smears than CC preparations. Conclusions: LBC is a better method than conventional smear for smear preparation and processing of aspirates obtained from lung and mediastinal mass.